SATISFACTION OF TRAINEES WITH FAMILY MEDICINE TRAINING PROGRAM: A CROSS SECTIONAL STUDY FROM QASSIM, SAUDI ARABIA - Rabbani, Unaib; Al-Gabbany, Saleh Abdelfatah; Jahan, Saulat; Kalevaru, Chandra Shekhar; Sulaiman, Amel Abdalrhim (Journal of Ayub Medical College Abbottabad, 2020)
Background: Focus on quality of postgraduate training has increased. One of the quality indicators is satisfaction of trainees with the residency programs. We aimed to assess the level of satisfaction of Saudi Board family medicine trainees with training program in Qassim. Methods: Anonymized online survey, using a structured questionnaire, was conducted among the current family medicine residents (n = 60) in Qassim in 2019. Descriptive analyses were carried out to calculate frequencies of the responses. Satisfaction level was compared between basic (R1, R2) and advance (R3, R4) levels using Chi-square test. Results: About 67% (40) were basic level trainees. A higher proportion (>80%) of trainees was satisfied with the program director. Satisfaction with trainers ranged 45% to 85% for different items. About 79% of the trainees were satisfied with the training program organization. In the domain of training processes higher proportion (73-83%) was satisfied with supervision and feedback while a lower proportion (63-68%) was satisfied with evaluations. Proportion of satisfied trainees in the domain of hospital rotations was lowest (43%) for academic activities in the hospitals. About family medicine rotations, a higher proportion (75%) was satisfied with academic activities. Higher proportion of trainees (78-86%) was satisfied with research facilitation and supervision. Mean score for overall satisfaction was 7.63 out of 10. Conclusion: The results of this study would help focus on certain domains to improve the quality of program. We recommend family medicine programs to regularly carry out such surveys for continuous quality improvement. Keywords: Family Medicine; Residents; Satisfaction; Training; Saudi Arabia